Rinderpest: The veterinary perspective on eradication - Roeder, P.; Mariner, Jeffrey C.; Kock, R. (Royal Society, 2013)
Rinderpest was a devastating disease of livestock responsible for continent-wide famine and poverty. Centuries of veterinary advances culminated in 2011 with the UN Food and Agriculture Organization and the World Organization for Animal Health declaring global eradication of rinderpest; only the second disease to be eradicated and the greatest veterinary achievement of our time. Conventional control measures, principally mass vaccination combined with zoosanitary procedures, led to substantial declines in the incidence of rinderpest. However, during the past decades, innovative strategies were deployed for the last mile to overcome diagnostic and surveillance challenges, unanticipated variations in virus pathogenicity, circulation of disease in wildlife populations and to service remote and nomadic communities in often-unstable states. This review provides an overview of these challenges, describes how they were overcome and identifies key factors for this success.